Strategic value‐directed learning and memory in Alzheimer's disease and behavioural‐variant frontotemporal dementia. Issue 2 (12th February 2018) - Wong, Stephanie; Irish, Muireann; Savage, Greg; Hodges, John R.; Piguet, Olivier; Hornberger, Michael
Abstract : In healthy adults, the ability to prioritize learning of highly valued information is supported by executive functions and enhances subsequent memory retrieval for this information. In Alzheimer's disease (AD) and behavioural‐variant frontotemporal dementia (bvFTD), marked deficits are evident in learning and memory, presenting in the context of executive dysfunction. It is unclear whether these patients show a typical memory bias for higher valued stimuli. We administered a value‐directed word‐list learning task to AD ( n = 10) and bvFTD ( n = 21) patients and age‐matched healthy controls ( n = 22). Each word was assigned a low, medium or high point value, and participants were instructed to maximize the number of points earned across three learning trials. Participants' memory for the words was assessed on a delayed recall trial, followed by a recognition test for the words and corresponding point values. Relative to controls, both patient groups showed poorer overall learning, delayed recall and recognition. Despite these impairments, patients with AD preferentially recalled high‐value words on learning trials and showed significant value‐directed enhancement of recognition memory for the words and points. Conversely, bvFTD patients did not prioritize recall of high‐value words during learning trials, and this reduced selectivity was related to inhibitory dysfunction. Nonetheless, bvFTD patients showed value‐directed enhancement of recognition memory for the point values, suggesting a mismatch between memory of high‐value information and the ability to apply this in a motivationally salient context. Our findings demonstrate that value‐directed enhancement of memory may persist to some degree in patients with dementia, despite pronounced deficits in learning and memory.